Corporate social responsibility disclosures in Malaysia: evidence from large companies - Sadou, Abdelkader; Alom, Fardous; Laluddin, Hayatullah (Emerald Publishing Limited, 2017)
Purpose – The purpose of this study is to examine whether there is any improvement in the extent and quality of corporate social responsibility disclosures (CSRD) in Malaysia between 2011 and 2014 and to determine the factors that influence the extent and quality of CSRD in these two years. Also, this study examines the methods of disclosures and the items that largest Malaysian companies addressed. Design/methodology/approach – A self-constructed CSR is utilised to measure the extent and quality of CSRD in the annual reports of the top 71 Malaysian companies listed in Bursa Malaysia for the years 2011 and 2014. Multiple regressions along with their associated toolkits for data verification and diagnostic tests are used to assess the improvement in CSRD between 2011 and 2014 and the factors that affect CSRD. Findings – Results show a slight increase in the extent and quality of CSRD between 2011 and 2014. With regards to the factors influencing CSRD, only awards are found to be significant in determining the extent and quality of CSRD either in 2011 or in 2014. Board size, ownership concentration, independent non-executives and return on assets influence both the extent and quality of CSRD in 2011. Director ownership and firm size determine the extent and quality of CSRD in 2014. Government ownership only influences the extent of CSRD in 2011. Research limitations/implications – Some traditional limitations are found to be considered in future research, such as the use of annual reports as the only source of CSRD information. Results support the legitimacy theory that assumes that Malaysian companies disclose CSR information as a reflection of the incidents that happen in that environment of the firm without ignoring the role of the government in pushing those companies towards being socially responsible by issuing regulations, or in motivating those companies by introducing awards and giving fiscal facilities. Practical implications – The results help the policymakers to introduce more awards in some domains that were less addressed by Malaysian companies and also to examine the causes behind the non-influence of the new Malaysian Code on Corporate Governance (MCCG 2012) on CSRD. Originality/value – The study can be considered as one of the limited empirical studies that assess the changes in CSRD before and after the issuance of MCCG 2012 in Malaysia.